Research history and conservation biological evaluation of the Orthopter fauna of Hortobágy National Park - Nagy, Antal; Rácz, István András; Arnóczkyné Jakab, Dóra (JOURNAL OF LANDSCAPE ECOLOGY, 2019)
Due to its unique natural character and cultural values, the Hortobágy Natural Park is a very important region both on national and European level. First records on the Orthoptera fauna were published in the turn of the 20th century. Then in 1940’s Barnabás Nagy published his two volume summary of the Orthoptera fauna of the region under the title ‘A Hortobágy szöcske- és sáskavilága I-IL’ [The grasshopper and mantis world of the Hortobágy I-IL], After that, the intensity of orthopterological studies varied on a wide range. By this time most of our data become archaic and we do not know the real status of the regional fauna. First we collected the published (28 papers from 18 authors) and partly unpublished data (67 species, 62 habitats), than revealed the history of orthopterological studies, and revised the Orthoptera checklist. Based on the revised data set containing 62 species (among them 6 protected, 11 scattered and 8 rare in the Hungarian fauna) we set prioritisation for further faunal studies and made the conservation biological evaluation of the fauna. The sampling effort and the distribution of data showed large spatial heterogeneity. There are many poorly studied regions and species with rare (only 1-2) and/or old archaic data In 2016, we restarted the intensive quantitative samplings in the national park. During 2016 and 2017 more 2,5x2,5 km UTM quadrants were studied than during the last 15 years, which shows the effectiveness of the sampling strategy. In the near future the revision of unverified data and samplings of less studied regions should be carried out.
Keywords: Hortobágy National Park; Ensifera; Caelifera; fauna; UTM